Smart Agent and Modified Master-Backup Algorithm for Auto Switching Dynamic Host Configuration Protocol Relay through Wireless Router - Syafei, Wahyul Amien; Soetrisno, Yosua Alvin Adi; Prasetijo, Agung Budi (International journal of communication networks and information security, 2022)
Several problems happened in a wireless router which is the number of clients that connected to DHCP (Dynamic Host Configuration Protocol) services and also durability in connectivity. Wireless router which is used in the office nowadays usually has a small memory and also CPU power. Memory or CPU sometimes could be running out when a wireless router does some background services. DHCP is one of the services needed to run in a wireless router. DHCP is interrupted when memory or CPU is full. DHCP relay and modification of the backup algorithm needed to overcome this situation when the memory or CPU in the wireless router is limited. The modification of the backup algorithm is a mechanism to switch the main router with the backup router when the main router memory is busy. DHCP relay could become a DHCP server directly when the main router is busy. Wireless router in another side could be formatted with open-source OS such as OpenWRT to become bridge interface that connected to DHCP relay. The scenario that tested in this research is using Cisco DHCP relay services in combination with OpenWRT wireless router, in variation with Mikrotik original “capsman” protocol with DHCP relay in combination with wireless-enabled Mikrotik and also in combination with OpenWRT wireless router. The result shows that OpenWRT in configuration with DHCP relay and backup algorithm could extend the number of a client connected, and also the durability of the wireless router runs its services as DHCP forwarder to DHCP relay and DHCP server. Theoretically, the number of the client that could connect in class C IPv4 address is 253 clients. Practically, in some wireless router brand, the number of the client is limited to 15 to 30 clients because that number is an optimal client for consuming the bandwidth. DHCP relay scenario could extend that limit to have a larger number of the client, and the new backup algorithm in combination also doesn’t decrease IP release time significantly from usual DHCP using a direct connection.